Stability study of hydrogen-air flame in a conical porous burner. (15th January 2021) - Zangeneh, Vahid; Alipoor, Alireza
Abstract: Porous medium combustion offers several advantages such as extended flammability limits, high burning rates and low pollutant emissions. In this work, laminar premixed flame of hydrogen/air mixture in a conical porous burner is numerically investigated by using OpenFOAM CFD toolbox. An unsteady, two-dimensional mathematical model is constructed. Flame front location within the burner is not predetermined in this model. A baseline case is first investigated using detailed kinetics for hydrogen combustion. Flame stability analysis is then performed and the effect of the burner cone angle on flame location is studied. For this purpose, four different burner cone angles with seven different firing rates are examined. It is observed that the burner cone angle has no considerable effect on flashback and blowout limits. Variation of the flame location in the porous medium with the burner cone angle and firing rate is also investigated. It is concluded that increasing the firing rate for a fixed burner cone angle, moves the flame location downstream in the burner and also increases the length of the preheating zone. On the other hand, an increase in the burner cone angle at a fixed firing rate causes the flame to move upstream and also shortens the preheating zone length. Highlights: Laminar premixed hydrogen/air combustion in a conical porous burner is numerically investigated. The effect of the burner cone angle on flame location is studied. Increasing of firing rate causes flame location moves toward downstream. Preheating zone length will be shorten with increasing of the burner cone angle.